2014
DOI: 10.1111/1460-6984.12105
|View full text |Cite
|
Sign up to set email alerts
|

Semantic trouble sources and their repair in conversations affected by Parkinson's disease

Abstract: BackgroundIt is known that dysarthria arising from Parkinson's disease may affect intelligibility in conversational interaction. Research has also shown that Parkinson's disease may affect cognition and cause word-retrieval difficulties and pragmatic problems in the use of language. However, it is not known whether or how these problems become manifest in everyday conversations or how conversation partners handle such problems.AimsTo describe the pragmatic problems related to the use of words that occur in eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 45 publications
3
33
1
Order By: Relevance
“…Word-finding problems in people with PD have also been found to impact conversational interaction quite substantially. In a study by Saldert et al [20] it was shown that 70% of instances of other-initiated repairs were caused by word-finding problems or atypical wording by the conversation partner with PD. Typically, the non-impaired conversation partner either rephrased the utterance or suggested a way to express what the intended meaning could be in some other collaborative way.…”
Section: Discussionmentioning
confidence: 99%
“…Word-finding problems in people with PD have also been found to impact conversational interaction quite substantially. In a study by Saldert et al [20] it was shown that 70% of instances of other-initiated repairs were caused by word-finding problems or atypical wording by the conversation partner with PD. Typically, the non-impaired conversation partner either rephrased the utterance or suggested a way to express what the intended meaning could be in some other collaborative way.…”
Section: Discussionmentioning
confidence: 99%
“…The functional anomalies related to behavior or intelligence is highly governed by the implication of cognitive attributes in human [44]. The major cognitive differences a physician trace in the early stage of PD includes abnormalities in execution of functions, attention difficulties, slow thinking, trouble in word selection, difficulties in remembering information, learning, hampered spatial learning and imaging capability [45,46].…”
Section: Types Of Cognitive Impairmentsmentioning
confidence: 99%
“…Saldert et al 53 and Griffiths et al 54 examined in detail naturally occurring conversations between PD patients and nonimpaired others (Griffiths et al 55 for a more general discussion on the use of CA for analyzing PD interactional difficulties). These interactions were recorded and analyzed using common CA techniques.…”
Section: Pragmatic Production Deficits In Pdmentioning
confidence: 99%
“…And, in fact, this difficulty appears to frequently result in the deletion of PD turns at talk. Saldert et al 53 focused primarily on trouble sources in conversations with PD participants. An important contribution of their work was the identification of cognitive difficulties as contributing to the initiation of repair sequences.…”
Section: Pragmatic Production Deficits In Pdmentioning
confidence: 99%